2018
DOI: 10.1007/s12253-018-0464-y
|View full text |Cite
|
Sign up to set email alerts
|

Ki67 and P53 in Relation to Disease Progression in Metastatic Pancreatic Cancer: a Single Institution Analysis

Abstract: We investigated the expression patterns of Ki67 and p53 in metastatic pancreatic adenocarcinomas and analyzed their relationship with disease progression-free survival (PFS) and overall survival (OS) in the overall study population and in patients treated with a gemcitabine-containing chemotherapy versus FOLFIRINOX chemotherapy. Patients with histologically confirmed stage IV adenocarcinoma of the pancreas treated at AUBMC were included after obtaining institutional review board approval (IRB ID: IM.ST.05). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 24 publications
0
16
1
Order By: Relevance
“…Several tissue markers have been proposed to have a prognostic impact on PC. As such, GATA6 expression allows a distinction between classical and basal-like subtypes [ 26 ]—with the latter being associated with chemoresistance and poor prognosis [ 27 , 28 , 29 ], while a high Ki-67 proliferation index is considered to have a negative impact on disease-free survival [ 30 , 31 , 32 ]. All available PDOs with the corresponding tumor tissue were evaluated for GATA6 and Ki-67 expression by immunohistochemistry ( Figure 4 A,D).…”
Section: Resultsmentioning
confidence: 99%
“…Several tissue markers have been proposed to have a prognostic impact on PC. As such, GATA6 expression allows a distinction between classical and basal-like subtypes [ 26 ]—with the latter being associated with chemoresistance and poor prognosis [ 27 , 28 , 29 ], while a high Ki-67 proliferation index is considered to have a negative impact on disease-free survival [ 30 , 31 , 32 ]. All available PDOs with the corresponding tumor tissue were evaluated for GATA6 and Ki-67 expression by immunohistochemistry ( Figure 4 A,D).…”
Section: Resultsmentioning
confidence: 99%
“…As showed in Figure 7A and B, co-administration of FMT and CpG significantly suppressed the tumor growth in tumor-bearing mice. Ki-67, an antigen present in the nuclei of proliferating cells, is widely used to evaluate the proliferative activity of tumors 40. The immunohistochemical analysis revealed that the percentage of Ki-67- and EGFR-positive tumor cells in the FMT/CpG group was markedly lower than that in the control group (Figure 7D and E), whereas the percentage of M1 macrophages stained with F4/80 and iNOS in tumor tissues was significantly up-regulated (Figure 7F).…”
Section: Resultsmentioning
confidence: 99%
“…The tumor also had a Ki67 index of 30%, with positive reactivity for P53, indicative of a relatively poor prognosis. [16]…”
Section: Discussionmentioning
confidence: 99%